AnATLyzer: an advanced IDE for ATL model transformations - Cuadrado, Jesús Sánchez; Guerra, Esther; de Lara, Juan (2018 IEEE/ACM 40th International Conference on Software Engineering: Companion (ICSE-Companion), 2018)
Model transformations (MTs) are key in model-driven engineering as they automate model manipulation. Their early verification is essential because a bug in a MT may affect many projects using it. Still, there is a lack of analysis tools applicable to non-toy transformations developed with practical MT languages. To alleviate this problem, this paper presents AnATLyzer: a static analysis tool for ATL MTs. The tool is able to detect a wide range of non-trivial problems in ATL transformations by using constraint solving to improve the analysis precision. It provides a live environment integrated into Eclipse which allows checking and fixing problems as the transformation is written. The environment is highly configurable and provides facilities like quick fixes, visualizations, navigation shortcuts and problem explanations. We have evaluated the tool over third-party MTs, obtaining good results. The tool website is http://anatlyzer.github.io, and a video showcasing its features is at https://youtu.be/bFpbZht7bqY